Long-term Use of Topical Bimatoprost on Rhododendrol-induced Refractory Leukoderma: A Case Report - Saki Fukaya; Masahiro Kamata; Tomoko Kasanuki; Makoto Yokobori; Shintaro Takeoka; Kotaro Hayashi; Takamitsu Tanaka; Atsuko Fukuyasu; Takeko Ishikawa; Takamitsu Ohnishi; Satoshi Iimuro; Shinichi Watanabe; et al. (Medical Journals Sweden, 2019)
Abstract is missing (Short communication)